Telecom single-photon emitters in GaN operating at room temperature: Embedment into bullseye antennas - Meunier, Max (2023)
The ideal single-photon source displaying high brightness and purity, emission on-demand, mature integration, practical communication wavelength (i.e., in the telecom range), and operating at room temperature does not exist yet. In 2018, a new single-photon source was discovered in gallium nitride (GaN) showing high potential thanks to its telecom wavelength emission, record-high brightness, good purity, and operation at room temperature. Despite all these assets, its coupling to photonic structures has not been achieved so far. In this article, we make a first step in this direction. First, we analyze whether stacking faults are indeed a necessary condition for obtaining such emitters in GaN layers. Then, we discuss the challenges associated to a low spatial density and to a spectrally wide distribution of emitters, which necessitate their location to be determined beforehand and the photonic structure resonance to be tuned to their emission wavelength. The design and fabrication of bullseye antennas are thoroughly described. Finally, we fabricate such bullseyes around telecom emitters and demonstrate that the embedded emitters are able to sustain the necessary clean-room process and still operate as single-photon emitters after the fabrication steps, with room-temperature purities up to 99% combined with repetition rates in the order of hundreds of kHz. The findings in this work demonstrate that telecom single-photon emitters in GaN operating at room temperature are well adapted for single-photon applications where brightness and purity are the required figures of merit, but highlight the numerous difficulties that still need to be overcome before they can be exploited in actual quantum photonic applications.